Соло трех дам: лирические фантазии / Н. П. Иевлев - Иевлев Николай Павлович (Удмуртия, 2005)
Экземпляры: Ф. 4 (20190723) / Инвентарный номер: 46173 / Цена: 100.00 / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: И 30 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6-4